If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(B + 9) = 36 Reorder the terms: 3(9 + B) = 36 (9 * 3 + B * 3) = 36 (27 + 3B) = 36 Solving 27 + 3B = 36 Solving for variable 'B'. Move all terms containing B to the left, all other terms to the right. Add '-27' to each side of the equation. 27 + -27 + 3B = 36 + -27 Combine like terms: 27 + -27 = 0 0 + 3B = 36 + -27 3B = 36 + -27 Combine like terms: 36 + -27 = 9 3B = 9 Divide each side by '3'. B = 3 Simplifying B = 3
| s+28=20 | | 2y^2+6y-8=0 | | ax=x+a | | 2/3z=41/4 | | 5(3v-7)+2(3v+2)=74 | | 3x+11y=29 | | 5x+3x-5=35 | | 20x^2+9x-1=0 | | 4x-3x+8=7x-3-6x | | 4-4/5(4G+3)=-24 | | 3(5u-2)+4(2u+7)=68 | | 2/5=4/5c | | 3(5u-2)+4(2u+7)=63 | | (3p^2+4p+5)/p | | 3/8n=-1/4 | | -10=11-7x | | 4.6q-2.8-4.3q=-0.7q-2.4 | | 3/7g=9 | | 2(7l+8)+3(2l-1)=93 | | -10+4y=14 | | 167-4x=41x+17 | | y-2=-12 | | -3x+4(2.5)=40 | | 4(3z+4)+3(2z-3)=61 | | bx+b=0 | | 2(t+3)+9(2t-1)=19(t-1)-5 | | 4(3y+2)+5(2y+3)=111 | | -3=3x+7 | | (x-4)6=18 | | -3(3x+2)=2x+6 | | z^2-11z-12= | | 9x-4(3)=-30 |